2017
DOI: 10.26681/jote.2017.010106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Service Learning in Haiti on the Cultural Competence of OTD Students

Abstract: As society trends towards increased cultural diversity, the need for cultural competence in the field of occupational therapy (OT) becomes more acute. Immersion in another culture within the curriculum offers the student an opportunity to put their knowledge into practice and recognize the need to competently interact with members of another culture. This study explored the impact of a service learning trip to Haiti, providing seating and mobility services, on all four factors of cultural intelligence (CQ; i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Increased understanding and appreciation of disability issues was demonstrated in a study involving a community project investigating accessibility (Gitlow & Flecky, 2005). Short and St. Peters (2017) found improved cultural competence for OTD students who provided seating and mobility services during a service learning experience in Haiti. Greene (1997) also reported the impact on the psychosocial development of occupational therapy students who participated in a service learning experience, specifically appreciation for dignity, quality, and justice.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Increased understanding and appreciation of disability issues was demonstrated in a study involving a community project investigating accessibility (Gitlow & Flecky, 2005). Short and St. Peters (2017) found improved cultural competence for OTD students who provided seating and mobility services during a service learning experience in Haiti. Greene (1997) also reported the impact on the psychosocial development of occupational therapy students who participated in a service learning experience, specifically appreciation for dignity, quality, and justice.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Additionally, OTs should utilize self-awareness to evaluate the impact of their own beliefs and perceptions during cross-cultural interactions and apply that knowledge to clinical practice (Talero et al, 2015). Short and St. Peters (2017) found that a goal-directed ISL experience involving the provision of seating and mobility services in Haiti had a short-term (immediate) impact on OTD students' (n=10) cultural intelligence as a construct of cultural competence. The purpose of the current study was to confirm the short-term impact of ISL on cultural intelligence with a larger sample (N=40) and examine long-term impact at six-month, one-year, two-year, and three-year intervals following the initial experience (Short & St. Peters, 2017).…”
Section: International Service-learning and Cultural Competence In Ocmentioning
confidence: 94%
“…Short and St. Peters (2017) found that a goal-directed ISL experience involving the provision of seating and mobility services in Haiti had a short-term (immediate) impact on OTD students' (n=10) cultural intelligence as a construct of cultural competence. The purpose of the current study was to confirm the short-term impact of ISL on cultural intelligence with a larger sample (N=40) and examine long-term impact at six-month, one-year, two-year, and three-year intervals following the initial experience (Short & St. Peters, 2017). Qualitative data was also collected to highlight the participants' perceptions regarding the impact of the experience.…”
Section: International Service-learning and Cultural Competence In Ocmentioning
confidence: 94%
See 2 more Smart Citations